Biomaterials from blends of fluoropolymers and corn starch-implant and structural aspects - Pereira, Joao D. A. S. [UNESP]; Camargo, Regina C. T. [UNESP]; Filho, Jose C. S. C. [UNESP]; Alves, Neri [UNESP]; Rodriguez-Perez, Miguel A.; Constantino, Carlos J. L. [UNESP] (Elsevier B.V., 2014)
The development of polymeric blends to be used as matrices for bone regeneration is a hot topic nowadays. In this article we report on the blends composed by corn starch and poly(vinylidene fluoride), PVDF, or poly(vinylidene fluoride-trifluoroethylene), P(VDF-TrFE), to obtain biocompatible materials. Blends were produced by compressing/annealing and chemically/structurally characterized by micro-Raman scattering and Fourier transform infrared (FTIR) absorption spectroscopies, dynamic mechanical analysis (DMA) and scanning electron microscopy (SEM), besides in vivo study to evaluate the tissue response. Vibrational spectroscopy reveals no chemical interaction between the polymers and starch, absence of material degradation due to compressing/annealing process or organism implantation, and maintenance of a and ferroelectric crystalline phases of PVDF and P(VDF-TrFE), respectively. As a consequence of absence of interaction between polymers and starch, it was possible to identify by SEM each material, with starch acting as filler. Elastic modulus (E') obtained from DMA measurement, independent of the material proportion used in blends, reaches values close to those of cancellous bone. Finally, the in vivo study in animals shows that the blends, regardless of the composition, were tolerated by cancellous bone. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Poly(vinylidene fluoride); Poly(vinylidene fluoride-trifluoroethylene); Corn starch; Bone healing